Control of hepatocyte proliferation and survival by Fgf receptors is essential for liver regeneration in mice. Issue 9 (21st November 2014) - Padrissa-Altés, Susagna; Bachofner, Marc; Bogorad, Roman L; Pohlmeier, Lea; Rossolini, Thomas; Böhm, Friederike; Liebisch, Gerhard; Hellerbrand, Claus; Koteliansky, Victor; Speicher, Tobias; Werner, Sabine
Abstract : Objective: Fibroblast growth factors (Fgfs) are key orchestrators of development, and a role of Fgfs in tissue repair is emerging. Here we studied the consequences of inducible loss of Fgf receptor (Fgfr) 4, the major Fgf receptor (Fgfr) on hepatocytes, alone or in combination with Fgfr1 and Fgfr2, for liver regeneration after PH. Design: We used siRNA delivered via nanoparticles combined with liver-specific gene knockout to study Fgfr function in liver regeneration. Liver or blood samples were analysed using histology, immunohistochemistry, real-time RT-PCR, western blotting and ELISA. Results: siRNA-mediated knockdown of Fgfr4 severely affected liver regeneration due to impairment of hepatocyte proliferation combined with liver necrosis. Mechanistically, the proliferation defect resulted from inhibition of an Fgf15-Fgfr4-Stat3 signalling pathway, which is required for injury-induced expression of the Foxm1 transcription factor and subsequent cell cycle progression, while elevated levels of intrahepatic toxic bile acids were identified as the likely cause of the necrotic damage. Failure of liver mass restoration in Fgfr4 knockdown mice was prevented at least in part by compensatory hypertrophy of hepatocytes. Most importantly, our data revealed partially redundant functions of Fgf receptors in the liver, since knockdown of Fgfr4 in mice lacking Fgfr1 and Fgfr2 in hepatocytes caused liver failure after PH due to severe liver necrosis and a defect in regeneration. Conclusions: These results demonstrate that Fgfr signalling in hepatocytes is essential for liver regeneration and suggest activation of Fgfr signalling as a promising approach for the improvement of the liver's regenerative capacity.